2008 16th IEEE International Conference on Program Comprehension 2008
DOI: 10.1109/icpc.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Domain Terms in Source Code

Abstract: Information about the problem domain of the software and the solution it implements is often embedded by developers in comments and identifiers. When using software developed by others or when are new to a project, programmers know little about how domain information is reflected in the source code. Programmers often learn about the domain from external sources such as books, articles, etc. Hence, it is important to use in comments and identifiers terms that are commonly known in the domain literature, as it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 23 publications
(16 reference statements)
1
44
0
Order By: Relevance
“…These names often serve as a starting point in many program comprehension tasks (Caprile and Tonella 1999;Haiduc and Marcus 2008;Abebe et al 2009;Arnaoudova et al 2010). Hence, it is essential that these names clearly reflect the concepts that they are supposed to represent, as self-documenting identifiers decrease the time and effort needed to acquire a basic comprehension level for a programming task Binkley et al 2009).…”
Section: Conceptual Information In Softwarementioning
confidence: 99%
“…These names often serve as a starting point in many program comprehension tasks (Caprile and Tonella 1999;Haiduc and Marcus 2008;Abebe et al 2009;Arnaoudova et al 2010). Hence, it is essential that these names clearly reflect the concepts that they are supposed to represent, as self-documenting identifiers decrease the time and effort needed to acquire a basic comprehension level for a programming task Binkley et al 2009).…”
Section: Conceptual Information In Softwarementioning
confidence: 99%
“…The authors' observations on the missing links was: (1) it was difficult to do some of the tracing because the documents/requirements were incomplete, ambiguous and (2) unknown acronyms hindered the trace recovery process. Haiduc and Marcus [Haiduc and Marcus(2008)] studied several open-source systems and found that about 40% of the domain terms are being used in the source code by developers. If the domain terms are ambiguous, it will also impact source code as well.…”
Section: Ambiguous Requirementsmentioning
confidence: 99%
“…Therefore, we assume that two code fragments that contain identifiers belonging to the same concept might provide the same functionality and could, therefore, be potential re-implementations. This assumption is strengthened by Haiduc and Marcus [13]. …”
Section: General Approachmentioning
confidence: 87%